Does inter-provincial energy exportation affect local energy affordability? Evidence from China - Jin Zhang; Zheng Wang (Energy Reports, 2022)
Through inter-provincial energy exportation, the coal resource-based area (CRA) makes a significant contribution to ensuring domestic energy security in China. However, CRA suffers from energy poverty itself. To investigate whether inter-provincial energy exportation can mitigate local energy poverty, this study focuses on the improvement of local energy affordability to mitigate energy poverty because adequate energy access has been achieved in China. Based on panel data of five provinces in CRA covering the period of 2000–2018, we estimate the impact of inter-provincial energy exportation on local energy affordability as well as the moderating effect of industrial structure upgrading on this impact. The results show that energy affordability in CRA is generally weaker than the national average, and energy affordability in rural areas is weaker than that in urban areas. Meanwhile, inter-provincial energy exportation poses an inverted U-shaped impact on local energy affordability, and because energy exportation structure positively affects local energy affordability, an increase in the share of electricity in total energy exportation by 1% can lead to a 0.05% improvement in local energy affordability. Furthermore, industrial structure upgrading plays a limited role in local energy affordability improvement, which is because the tertiary industry poses a negative moderating effect on this inverted U-shaped impact. These findings have important policy implications for adjusting inter-provincial energy exports and optimizing the industrial structure in CRA.